SECTORAL VOLATILITY AND NATIONAL OUTPUT FLUCTUATIONS IN THE INDONESIAN ECONOMIC REGION - Padli Pawaid Yahya; Azizah , Lina; Choiri, Miftakhul (International Journal of Economics, Business, and Entrepreneurship, 2025)
ADF unit root test is used to check the stationarity of the data. Autoregressive Conditional Heteroscedasticity (ARCH) and General Autoregressive Conditional Heteroscedasticity (GARCH) are used to estimate the volatility of GDP and sectoral growth rates. To see the impact of sectoral volatility on economic growth rate, Ordinary Least Square (OLS) is used. The results of this study explain the greater volatility of the economic growth rate. The exports, imports, utilities, and services sectors also fluctuate more. The results also show that the output growth rate in the delayed period, the agricultural sector, and the manufacturing sector do not have a strong influence on the output growth rate in the current period. Furthermore, the results show that volatility in the government consumption sector contributes the highest to the volatility of the economic growth rate compared to other sectors. Practical Implications for Economic Growth and Development: This study empirically investigates the impact of sectoral volatility on Indonesia's economic growth using annual time series data for the period 2011Q2 to 2023Q2. This study also attempts to determine the extent of the implications of volatility on Indonesia's economic growth rate with varying variance across sectors.